Determination Of Macro Mineral Content In Fresh Noni Fruit (Morinda Citrifolia L.) By Atomic Absorption Spectrophotometry - Novranda Pertiwi, Nia; De Lux Putra, Effendy; Rahman Harun, Fathur (International Journal of Science, Technology & Management, 2022)
This study aims to determine the levels of macro minerals such as potassium, calcium, sodium, and magnesium in fresh noni fruit. The sample of noni fruit was destructed, then quantitative analysis of potassium, calcium, sodium, and magnesium were performed using atomic absorption spectrophotometry (AAS) at a wavelength 766.5 nm for potassium; 422.7 nm for calcium; 589.0 nm for sodium; and 285.2 nm for magnesium. The advantages of this method are selective and sensitive. The average % recoveries were obtained in 109.7 % for potassium; 96.4 % for calcium; 99.7 % for sodium; and 92.4 % for magnesium. This method is very suitable for determining mineral content in fruit as shown in the recovery results and in accordance with the validation requirements.